Una historia de la actividad societaria en Antioquia (2021)
New elements to understand the reasons that allowed this region to achieve important business development were found in an investigation by the School of Law. To date, the project has studied 3,276 commercial companies established in this region between 1887 and 1945. Thanks to the alliance between the Medellin Chamber of Commerce for Antioquia and the EAFIT University, it was possible to reconstruct, from old documents, the history of corporate activity in the region.